2017
DOI: 10.1111/ecog.03123
|View full text |Cite
|
Sign up to set email alerts
|

Used‐habitat calibration plots: a new procedure for validating species distribution, resource selection, and step‐selection models

Abstract: ‘Species distribution modeling’ was recently ranked as one of the top five ‘research fronts’ in ecology and the environmental sciences by ISI's Essential Science Indicators, reflecting the importance of predicting how species distributions will respond to anthropogenic change. Unfortunately, species distribution models (SDMs) often perform poorly when applied to novel environments. Compounding on this problem is the shortage of methods for evaluating SDMs (hence, we may be getting our predictions wrong and not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 67 publications
0
78
0
Order By: Relevance
“…As a final step, new data can be simulated from fitted models. Simulations can be used to obtain estimates of space use (i.e., the utilization distribution), identify corridors of high use, asses the power of the model (testing how well parameters can be recovered as a function of sample size), or perform model validation (Fieberg et al., ). Many packages that fit models also provide methods to simulate from fitted models (e.g., ctmm or moveHMM).…”
Section: Functionalitymentioning
confidence: 99%
“…As a final step, new data can be simulated from fitted models. Simulations can be used to obtain estimates of space use (i.e., the utilization distribution), identify corridors of high use, asses the power of the model (testing how well parameters can be recovered as a function of sample size), or perform model validation (Fieberg et al., ). Many packages that fit models also provide methods to simulate from fitted models (e.g., ctmm or moveHMM).…”
Section: Functionalitymentioning
confidence: 99%
“…Instrumental to this are novel approaches to model evaluation and validation (e.g., [75]) that are generally independent of model choice and response variable type.…”
Section: Box 3 Correlative Versus Mechanistic Modelsmentioning
confidence: 99%
“…Testing indices of performance (based on classification or on predicted probability/ suitability) Li and Guo 2013, Rapacciuolo et al 2014, Fieberg et al 2018 • Several propositions have been made to base model performance metrics on the predicted probability of occurrence and on model calibration, rather than on the success to predict presences and absences. • Probabilistic VS studies have shown that metrics based on presence-absence classification rates are limited by the probabilistic nature of the distribution (e.g.…”
Section: Stagementioning
confidence: 99%